Peningkatan Kemampuan Berpikir Kritis Mahasiswa dalam Kerangka Lesson Study Melalui Model Pembelajaran Berbasis Masalah - Dewi Ratnaningsih; Irawan Suprapto; Rahmat Prayogi (Universitas Muhammadiyah Kotabumi, 2022)
Lesson Study is considered effective to be used to improve the quality of learning. Lesson Study implementation can be assisted by the application of problem-based learning model (PBL). Through PBL students' critical thinking skills can be improved. The purpose of the research in this article is to increase students' critical thinking skills within the framework of Lesson Study through a problem-based learning model. The method used in this research is a qualitative-quantitative method with the type of action research. Qualitative data were obtained from observation sheets, while quantitative data were obtained from student learning outcomes. The success of research based on qualitative data if 80% of the implementation of learning is in accordance with the learning scenario, while the success of quantitative data is obtained if at least 65% of students get good grades. Based on the results of the research, 80% of learning activities are in accordance with the learning scenario, while students who score in a good category are 71.42%, which means more than 65%. From the learning process, several findings were obtained. The findings are: (1) the didactic challenge is a mandatory thing that must be presented in the implementation of learning; (2) didactic challenges must be contextual; (3) problem-based learning improves students' critical thinking skills.